Biphasic Tracheal Relaxation Induced by Higenamine and Nantenine From Nandina domestica THUNBERG - Takuro Ueki; Tatsuhiro Akaishi; Hidenobu Okumura; Tsuneo Morioka; Kazuho Abe (Elsevier, 2011)
We compared the effects of the extract from fruits of Nandina domestica THUNBERG (NDE) and its constituents, higenamine and nantenine, on contractile responses in isolated guineapig trachea. NDE (1 mg/ml) caused biphasic relaxation of the trachea precontracted with high-K+ stimulation: the fast component was blocked by propranolol and mimicked by higenamine; and the slow was resistant to propranolol and mimicked by nantenine. Ca2+-induced contraction under high-K+ stimulation was antagonized by nantenine or NDE + propranolol. These results suggest that NDE relaxes the trachea quickly through β-adrenoceptor stimulation by higenamine and slowly through Ca2+ antagonism by nantenine. Keywords:: Nandina domestica THUNBERG, tracheal relaxation, higenamine